Expression regulation of bacterial lipase genes: a review - Zha, Dai-ming; Yan, Yun-jun (Frontiers in Microbiology, 2025)
Microbial lipases constitute the primary source of commercialized and industrial lipases, and they are extensively utilized across numerous industrial sectors. Compared to fungal lipases, bacterial lipases catalyze a broader spectrum of reactions with higher activity, enhanced stability, and improved stress resistance. Among them, lipases from Pseudomonas and Burkholderia cepacia are among the most widely employed microbial lipases. Furthermore, bacterial extracellular lipases act as crucial virulence factors, playing a significant role in the pathogenesis of bacteria. However, the production of bacterial lipases is typically low, rendering them expensive in the market and insufficient to meet the substantial demand for industrial production. To achieve large-scale production of bacterial lipases, stable and efficient homologous expression has proven to be an effective strategy. However, elucidating how bacterial lipase genes are regulated is the initial step for developing stable and efficient homologous expression, and a pressing scientific challenge. To date, the regulatory mechanisms governing the expression of bacterial lipase genes remain unclear, significantly impeding the construction of robust and high-yield homologous expression systems. Concurrently, understanding these regulatory mechanisms can facilitate early diagnosis of lipase-related pathogenic bacterial infections, and aid in the development of novel antibacterial drugs. In this review, we summarized the advancements in understanding the expression regulation of bacterial lipase genes, including direct regulators, the quorum sensing (QS) system, the Gac/Rsm system and its related regulators, as well as other regulators. Additionally, based on our ongoing research, we also discussed potential research directions in this field, aiming to provide valuable insights for the construction of homologous expression systems with high-yield lipases.